DNA-based floristic survey of red algae (Rhodophyta) growing in the mesophotic coral ecosystems (MCEs) offshore of Tanegashima Island, northern Ryukyu Archipelago, Japan - Masahiro Suzuki; Ryuta Terada (PLoS ONE, 2025)
A molecular-based floristic survey of marine red algal biodiversity was conducted offshore Tanegashima Island, which is located at the northern end of mesophotic coral ecosystems (MCEs), in the Ryukyu Archipelago, Japan. This study provides the first comprehensive catalog of red algae comprising the sublittoral marine flora of offshore Tanegashima Island, Japan, and represents the first exhaustive molecular-assisted survey of red algal marine flora in Japan. Morphological and molecular analyses using plastid-encoded rbcL and mitochondrion-encoded cox1 genes revealed a total of 129 species, which included nine newly recognized species in Japan. Morphologically, 82 species were assigned to known species. Among the 82 species, 17 included cryptic species, and 25 appeared to have misapplied names. The remaining 47 species could not be identified to the species level, which indicates the necessity of a detailed reference library containing validated DNA barcodes and further taxonomic studies based on morpho-molecular analyses.